Biodiversity and Nutrition Availability in a Matriarchal System in West Sumatra - David, Wahyudi; Kasim, Anwar; Ploeger, Angelika (Pakistan Journal of Nutrition, 2013)
Meals are human creation that unconsciously represents the way in which part of the world they are living and based on they culture background. Recently, the issue about food is not only how to prepare it but as well as how to get nutritious food supporting human health from limited natural resources. From this view point, choosing food gives an insight not only on the nutrition itself but about cultural and environmental factors as well. The objective of this study is to investigate if biodiversity plays still an important role in supporting local food security and sustaining nutrition intake in a matriarchal system. The study was done in Minangkabau; in coastal area, hilly area and lake area of West Sumatera, Indonesia. Participatory Rural Appraisal (PRA) was used to investigate biodiversity and nutrition intake. Qualitative and quantitative research technique include: In-depth interview and survey were carried out. The data was coded and clustered by using MAXQDA10. The results indicate that the matriarchal system is still playing an important role in nutrition intake in Minangkabau. The mother plays important roles in kitchen activity, meal decision and land ownership, although she is not involved directly into farming. The mother plays important role to increase the nutrition intake in the household by using local food diversity or by cultivating spices in the backyard. Thus matriarchal system generates kitchen representing women activity and play still an important role in managing the farm to fork activities.